Pan-Cancer Analysis Based on EPOR Expression With Potential Value in Prognosis and Tumor Immunity in 33 Tumors - Zhang, Yajing; Wang, Senyu; Han, Songtao; Feng, Yangchun (Frontiers in Oncology, 2022)
Background Erythropoietin receptor (EPOR), a member of the cytokine class I receptor family, mediates erythropoietin (EPO)-induced erythroblast proliferation and differentiation, but its significance goes beyond that. The expression and prognosis of EPOR in cancer remain unclear. Methods This study intended to perform a pan-cancer analysis of EPOR by bioinformatics methods. Several databases such as GTEx, TCGA, CCLE, and others were used to explore the overall situation of EPOR expression, and the correlation of EPOR expression with prognosis, microRNAs (miRNAs), immune infiltration, tumor microenvironment, immune checkpoint genes, chemokines, tumor mutation burden (TMB), microsatellite instability (MSI), methyltransferases, and DNA mismatch repair (MMR) genes in 33 tumors was analyzed. In addition, we compared the promoter methylation levels of EPOR in cancer tissues with those in normal tissues and performed protein–protein interaction network, gene–disease network, and genetic alteration analyses of EPOR, and finally enrichment analysis of EPOR-interacting proteins, co-expressed genes, and differentially expressed genes. Results The TCGA database showed that EPOR expression was upregulated in BLCA, CHOL, HNSC, KIRC, LIHC, STAD, and THCA and downregulated in LUAD and LUSC. After combining the GTEx database, EPOR expression was found to be downregulated in 18 cancer tissues and upregulated in 6 cancer tissues. The CCLE database showed that EPOR expression was highest in LAML cell lines and lowest in HNSC cell lines. Survival analysis showed that high EPOR expression was positively correlated with OS in LUAD and PAAD and negatively correlated with OS in COAD, KIRC, and MESO. Moreover, EPOR had a good prognostic ability for COAD, LUAD, MESO, and PAAD and also influenced progression-free survival, disease-specific survival, disease-free survival, and progression-free interval in specific tumors. Further, EPOR was found to play a non-negligible role in tumor immunity, and a correlation of EPOR with miRNAs, TMB, MSI, and MMR genes and methyltransferases was confirmed to some extent. In addition, the enrichment analysis revealed that EPOR is involved in multiple cancer-related pathways. Conclusion The general situation of EPOR expression in cancer provided a valuable clinical reference. EPOR may be target gene of hsa-miR-575, etc. A pan-cancer analysis of panoramic schema revealed that EPOR not only may play an important role in mediating EPO-induced erythroblast proliferation and differentiation but also has potential value in tumor immunity and is expected to be a prognostic marker for specific cancers.